Quizizz Video Responses Reveal Patterns in Students’ English Speaking Performance - Florentine Ananda RatnaNegara; Fika Megawati (Academia Open, 2025)
General Background: English speaking ability is a core productive skill essential for effective communication and academic readiness in a global context. Specific Background: Interactive platforms such as Quizizz provide gamified environments and video response features that allow students to practice oral language in flexible settings. Knowledge Gap: Prior studies have emphasized reading or grammar outcomes, leaving limited understanding of how Quizizz supports specific dimensions of speaking performance. Aims: This study explores junior high school students’ speaking performance through Quizizz video responses across fluency, vocabulary, grammar, and pronunciation using qualitative content analysis. Results: Findings indicate generally good fluency, vocabulary use, and pronunciation, while grammar remains the weakest component for most students; the video feature promotes confidence and participation. Novelty: The research offers an in-depth qualitative examination of authentic student speech recorded through a gamified platform rather than traditional classroom observation. Implications: The findings suggest that interactive video-based assessment can facilitate communicative practice while highlighting the need for complementary instruction in grammatical accuracy. Highlights: Learners demonstrated smooth delivery and intelligible articulation in most recorded tasks. Sentence structure accuracy showed frequent problems despite understandable messages. Recorded submissions encouraged participation and reduced hesitation during oral tasks. Keywords: Quizizz; Speaking Performance; Video Response; Gamified Learning; English Language Learning